Peran Kepemimpinan Dalam Meningkatkan Kinerja Prajurit Komando Rayon Militer 1407-19/Kahu Kabupaten Bone - Fitriani, Fitriani; Tahir, Muhammad; Parawu, Hafiz Elfiansya (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the role of Danramil leadership in improving the performance of soldiers from the Military District Command 1407-19/Kahu, Bone Regency. This study used qualitative methods and the data sources used were observations, interviews, other data sources and secondary data sources. The results of this study regarded the role of Danramil leadership were quite good, seen in (1) Danramil planning made an agenda, implementing, completing, planning work programs, training activities, coaching and controlling all soldiers, 2) organizing was carried out by Danramil could be seen at several activities of designing, grouping, organizing, dividing tasks, creating a comfortable working atmosphere and being able to manage aspects of existing personnel and facilities, 3) providing motivation had become an obligation by Danramil to carry out their capacity as a leader properly, 4) Danramil supervision could ensure the entire series of activities that had been planned, organized and implemented according to the plan, and it was a phase where Danramil could assess whether the goals that have been achieved were satisfactory or not, 5) Danramil evaluation was carried out every week on Friday, and there it could be seen what shortcomings and obstacles faced during the execution of the duties of the soldiers.Keywords: Leadership, Koramil Performance